2017
DOI: 10.1038/s41467-017-00463-1
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of native peptide sequences in prebiotic replication networks

Abstract: Biopolymer syntheses in living cells are perfected by an elaborate error correction machinery, which was not applicable during polymerization on early Earth. Scientists are consequently striving to identify mechanisms by which functional polymers were selected and further amplified from complex prebiotic mixtures. Here we show the instrumental role of non-enzymatic replication in the enrichment of certain product(s). To this end, we analyzed a complex web of reactions in β-sheet peptide networks, focusing on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 61 publications
3
48
0
Order By: Relevance
“…In terms of chemical replication, previous studies have shown that a peptide amyloid can act as a template to accelerate the rate of condensation (via native chemical ligation) of two smaller peptides that comprise the amyloidogenic peptide 14 , 15 . Very recently, this concept was extended to include an interconverting network of 4 regio- and stereoisomers in which the parent amyloid acted as a template to enhance the yield of self-products at the expense of kinetically more favorable products 16 . Considering the structure of the β-sheet 17 , 18 it is clear that as a template, an amyloid should be stereoselective.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of chemical replication, previous studies have shown that a peptide amyloid can act as a template to accelerate the rate of condensation (via native chemical ligation) of two smaller peptides that comprise the amyloidogenic peptide 14 , 15 . Very recently, this concept was extended to include an interconverting network of 4 regio- and stereoisomers in which the parent amyloid acted as a template to enhance the yield of self-products at the expense of kinetically more favorable products 16 . Considering the structure of the β-sheet 17 , 18 it is clear that as a template, an amyloid should be stereoselective.…”
Section: Introductionmentioning
confidence: 99%
“…The prebiotic relevance of the β-sheet networks and assemblies was recently highlighted by Tena-Solsona et al [ 17 ] who provided evidence for emergent catalytic behavior of self-assembled low-molecular-weight peptide aggregates, and by Nanda et al [ 21 ] who demonstrated error correction within replication networks through the emergence of short polymers exhibiting selective autocatalytic properties. Very recently, Rout et al [ 26 ] showed that an amyloid can direct the sequence-, regio-, and stereo-selective condensation of amino acid synthesis, and that the templating reaction is stable over a wide range of pH (5.6–8.6) and temperature (25–90 °C).…”
Section: Catalytic Amyloidsmentioning
confidence: 99%
“…In these same galleries the ammonia can go on to effect the amination of amino acids which may then polymerize to heterochiral peptides. Such peptides can act as nests to sequester functional anions and also to amalgamate to form amyloid . Note that on completion of the reductions green rust is normally oxidized to magnetite (Fe 3 O 4 ), hematite (Fe 2 O 3 ) and goethite (FeO[OH]) .…”
Section: What Does All This Have To Do With the Emergence Of Life?mentioning
confidence: 99%
“…Green rust is dosed with Ni and Co, intercalated with [MoS 4 ] 2− and often coated with phosphate . These functional elements are also found in proteins, as co‐factors, and are responsible for much of the bioenergetic transformations of extant biology, including electron bifurcation As in the redox proteins, green rust—poised between reduced alkaline hydrothermal solution and nitrate‐bearing acidulous ocean water—would physico‐chemically oscillate between reduced and oxidized states …”
Section: What Does All This Have To Do With the Emergence Of Life?mentioning
confidence: 99%